Childhood experiences of Filipino environmentalists a guide for developing environmental sensitivity - Recuenco, April Lou Pili (2007)
In the light of worldwide degradation, the protection and improvement of the environment have become an imperative educational goal. This descriptive study was conducted to investigate the lives of some renowned Filipino environmentalists. It involved 47 Filipino environmentalists across 3 different categories: government organization (GO), non-government organization (NGO), and the academe. Data were gathered through survey, case study with interview, and focus group discussion (FGD). Filipino environmentalists generally consider their childhood experiences as somehow influential in the development of their sensitivity to nature. Majority point out multiple sources of influence and these are experience of natural areas, education, people, membership in organizations, negative experiences, media and others.
"October 2007."
Thesis (M.A. Environmental Education)--University of the Philippines, Diliman.
Keywords: Environmental education -- Philippines -- Guidebooks; Environmentalists -- Philippines; Children and the environment -- Philippines